(3CUhGJ GdeYfjjf HGdcJGH GdeOQSj (B: (3hLgI fXQ CSGJPI GdJYdje GdKGfhj aj dHfGf HGdcJGH GdeOQSj GdQSejs - (3GdbhGU, YUeJs ((3HjQhJs (3GdgjFI GddHfGfjI ddYdhe GdJQHhjIs, 2007)
(3JYqHQ gPg GdeOGNdI Yf hLgI fXQ CSGJPI GdJYdje GdKGfhj aj dHfGf HGdcJGH GdeOQSj GdQSej GdUGOQ Yf GdeQcR GdJQHhj ddHMhK hGdEfeGA hGdeYJeO aj eNJda GdeOGQS GdQSejI haj fSHI cHjQI ef GdeOGQS GdNGUI CjVkG(B. (3hJbQ GdeOGNdI HCf GdcJH GdeOQSjI GddHfGfjI GdLOjOI JeKd JWhQkG dGaJkG bjGSkG Ydi eG SHbgG ef cJH TcdkG heVehfkG(B. (3heY Pdc aEfgG JTjQ Edi SdHjGJ cKjQI aj gPg GdcJH hefgG ZjGH GdTaGajI aj WQjbI JTcjd dLGf JCdja GdcJH GdeOQSjI eeG COi Edi JaGhJ aj GdeSJhi Hjf cJGH hBNQ ef LgI, hOGNd GdcJGH GdhGMO ef LgI CNQi, ceG XgQJ ghI Hjf eVehf GdcJGH GdeOQSj hHjf GdefgL GdOQGSj hGdCgOGa GdJQHhjI GdehVhYI(B. (3hJNdU GdeOGNdI Edi VQhQI GdGgJeGe HcJGH GddZI GdYQHjI NGUI, heQGLYJg fXGe GdJbjje GdeYJeO aj eNJda GdehGO GdOQGSjI, hEYGOI GdfXQ HGdeHGOiA hGdCSS GdeYJeOI ddSeGM HGSJNOGe GdcJH GdCLfHjI aj GdJYdje OGNd dHfGfs
(3GdfhY (B: (3aUd aj cJGHs
Keywords: Livres Scolaires; Public Sector Secondary Education; Secteur Public Cycle Secondaire; Textbooks; (3GdJYdje GdQSej GdeQMdI GdKGfhjIs; (3GdcJGH GdeOQSjs